Underwater Real-Time 3D Acoustical Imaging Theory, Algorithm and System Design - Chi, Cheng; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book presents the topic of underwater real-time 3-D acoustical imaging covering the theory, algorithms and system design. It summarizes recent advances in wideband and ultra-wideband underwater real-time 3-D acoustical imaging, which will be very useful for developing next-generation systems. Through simulation techniques, readers are able to quickly learn and develop practical underwater real-time 3-D acoustical imaging systems of their own.
Introduction to Underwater Real-Time 3-D Acoustical Imaging System -- Theory of 3-D Acoustical Imaging -- Large 2-D Array Design -- Real-time Imaging Algorithms -- System Design and Hardware Implementation -- Simulation Techniques for Developing 3-D Imaging Systems -- Summary and Future Prospects.
Keywords: Signal processing; Computer vision; Acoustics; Signal, Speech and Image Processing; Computer Vision; Acoustics